The relationship between diabetes self-care management and blood glucose level among type 2 diabetes mellitus patients - Dewi, Erika Untari; Widari, Ni Putu; Nursalam, Nursalam; Mahmudah, Mahmudah; Sari, Esti Yunita; Ning Susiana, Yohana Fransiska (Intelektual Pustaka Media Utama, 2023)
There are still many patients with diabetes mellitus (DM) with uncontrolled blood sugar levels. Self-care was needed to control blood glucose levels. The aim of this study was to analyze the relationship between diabetes self-care management and blood sugar levels in type 2 DM (T2DM) patients. This study was used a correlational design. Data was collected from the Internal Medicine Polyclinic of William Booth Hospital Surabaya. The dependent variable was blood glucose and the independent variable was diabetes self-care management. The 99 respondents were selected using the purposive sampling technique. The inclusion criteria were patients with T2DM, the ages between 45-and 64 age years old. We used the summary of diabetes self-care activities to assess self-care management and blood sugar level was measured using a capillary blood glucose test. Chi-square was used to calculate the relationship between diabetes self-care management and blood glucose level. This study showed that most of the respondents with good diabetes self-care management had good blood sugar levels and there was a significant relationship between diabetes self-care management and blood sugar levels among T2DM patients (p<0.05). Increasing diabetes self-care management among T2DM patients was required to control blood glucose levels.